Urgensi Pemberlakuan Undang-Undang Nomor 35 Tahun 2009 Terhadap Penyalahgunaan Narkotika Pada Masyarakat Indonesia - Azizah a; Andi Sabila Putri; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Narcotics abuse is a problem that often occurs in Indonesian society and is difficult to resolve because it can ensnare anyone from all walks of life. The perpetrator of the threat of Narcotics is someone who uses Narcotics illegally without having the right to use it and not because of official health reasons from a health expert. Narcotics when consumed illegally without rights and permits can have a bad impact on the abuser, such as giving the effect of dependence and addiction. In this research journal, we will be wrapped up in the dangers of narcotics in Indonesian society which are implemented by enforcing law in Law Number 35 of 2009 concerning Narcotics. The urgency of this research is the danger that will be obtained if there is Narcotics protection in Indonesian society with Law Number 35 of 2009 as a regulation that regulates it with various efforts to prevent and overcome the passage of Narcotics. The main purpose of this research is to examine, know, and clearly understand the dangers of the threat of Narcotics and the enactment of the Law on Narcotics. The research method applied in this study is qualitative-descriptive with a juridical-normative approach whose source is literature such as books, journals, scientific articles, and several other reading sources. The results of this study are efforts to prevent and overcome narcotics with the enactment of Law Number 35 of 2009 concerning Narcotics.